Effect of short duration integrated classroom yoga module on physical, cognitive, emotional and personality measures of school children - Atul Sinha; Sony Kumari (Wolters Kluwer Medknow Publications, 2021)
Context: Despite evidence of therapeutic benefits of yoga on school children, many schools do not include yoga in their daily schedule. Reasons cited are lack of time and resources. An efficacious short duration integrated classroom yoga module (ICYM) can overcome such problems. Aim: This study aimed to test the effect of such a yoga module on physical fitness, cognitive performance, emotional wellbeing, and personality characteristic of school children. Methods: The design was a randomized controlled trial with participants sourced from grades 7-10. The intervention period was 2 months. The primary outcome measures were 4 tests from the EUROFIT physical fitness testing battery, Stroop color-word naming task, Rosenberg self-esteem scale, WHO-5 wellbeing index, and Sushruta Child Personality Inventory. Statistical analysis used a repeated measure analysis of variance. Secondary outcome measure was a qualitative assessment. Results: The yoga group showed significant differences compared to the control group in 2 of 4 physical fitness variables, Stroop color-word naming task, and in the WHO-5 wellbeing index. Conclusion: ICYM is a validated, feasible, and efficacious school-based short-duration integrated yoga module. It can be considered for incorporation into the daily school schedule.